Ergonomics Intervention in Unit Blast Furnace of a Typical Steel Company - Majid Mo'tamed-Zadeh; Masoud Shafiei-Motlagh; Ebrahim Darvishi (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: Musculoskeletal disorders are a major part of occupational diseases in working environments. Prevention of the occurrence of these problems requires the use of ergonomic assessment techniques and intervention to improve working conditions. The purpose of this study was to investigate the prevalence of musculoskeletal disorders in workers in the blast furnace unit and the intervention to reduce the prevalence of these disorders. Materials & Methods: This study conducted on 24 people working in the furnace unit. Medical records of furnace workers were reviewed and Nordic Musculoskeletal Questionnaires (NMQ) was completed. Drilling operation and oxygenation task were assessed by using Rapid Entire Body Assessment (REBA) and workers were given the necessary training. Work stations of oxygenation for 24 workers were redesign and Drilling operation was mechanized. And employed workers with musculoskeletal disorders were changed. REBA and NMQ were used to reassess the intervention effects. Results: According to medical records and results of NMQ about 37.5 percent of workers had musculoskeletal disorders. REBA final score was 11 and 10 for the drilling and oxygenation tasks respectively. After redesigning the workstation, REBA final score was 5 for the oxygenation task and the drilling operation removed by mechanized. With the amendment procedures of musculoskeletal disorders was reduced 17.5 percent. Conclusion: According to REBA Score, the risk of musculoskeletal disorders was reduced by implementing amendments to the furnace unit and prevalence of musculoskeletal disorders also significantly reduced. Keyword: Ergonomic, MSDs, REBA, NMQ, Steel